PROFITABILITY AND CONSTRAINTS OF AGRICULTURAL COMMERCIALIZATION AMONG SMALLHOLDER RICE FARMERS IN NASARAWA STATE, NIGERIA - Usman, M. B.; Ademola, O. T.; Oni, B. O. (FUDMA Journal of Sciences, 2024)
This study analysed the profitability of smallholder rice farmers in Nasarawa State, Nigeria. Multistage sampling technique was used to select 300 rice farmers for the study. The primary data utilized for the study were collected using structured questionnaires. The data were analysed using descriptive statistics and farm budgetary techniques. The result of the study revealed that rice production in the study area is profitable with gross margin of N103, 876.17/ha. The most important problems identified were inadequate supportive institutions, poor access to credit, and poor rural infrastructure. Based on the findings of the study, it was recommended that provision of adequate and improved agricultural supportive institutions such as research, financial and marketing as well as extension services should be strengthened in order to improve smallholder rice profitability in the study area.